2022
DOI: 10.1007/s10903-022-01360-6
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Use in Refugee Primary Care: Implications for Care Beyond the COVID-19 Pandemic

Abstract: The expansion of telemedicine during the COVID-19 pandemic offers an opportunity to reach vulnerable refugee communities with limited access to healthcare; however, there are limited data on characteristics of refugee patients that are associated with telemedicine use. We examined primary care encounters between March 2020 and February 2021. We compared telemedicine encounters among refugee and non-refugee patients and examined patient characteristics associated with telemedicine use in refugee patients. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Despite substantial investment and an increasing number of DHTs available to health care consumers, their uptake has been limited among some population groups [8]. These include lower-socioeconomic-level groups and people from culturally and linguistically diverse (CaLD) communities, with the latter including racial or ethnic minority groups, immigrants and refugees, and First Nations people [8][9][10][11][12][13][14][15]. Studies have repeatedly reported that CaLD populations have lower uptake and use of DHTs than non-CaLD populations [8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantial investment and an increasing number of DHTs available to health care consumers, their uptake has been limited among some population groups [8]. These include lower-socioeconomic-level groups and people from culturally and linguistically diverse (CaLD) communities, with the latter including racial or ethnic minority groups, immigrants and refugees, and First Nations people [8][9][10][11][12][13][14][15]. Studies have repeatedly reported that CaLD populations have lower uptake and use of DHTs than non-CaLD populations [8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the migrant population has usually less stable employment conditions compared to the native population and migrants are overrepresented in a number of sectors such as the hospitality industry [ 23 ], it is very likely that immigrant women encountered more challenges to access telehealth services during the pandemic, such as the online version of prenatal courses. Similar groups, such as US refugees, showed having less access to telemedicine than non-refugees during the COVID-19 pandemic, mainly due to language barriers and other logistic issues [ 24 ]. Finally, women enrolled in Naples, with lower levels of education, housewives or unemployed as well as multiparous women were less likely to attend the prenatal course.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, providers worried that patients who did not speak English, had disabilities impacting their ability to use technology, or were from lower socioeconomic backgrounds faced more barriers with virtual visits. Previous studies have also found that telemedicine has worsened health care disparities due to difficulty accessing care (eg, people of color, non-English speakers, individuals with substance use disorders [31][32][33] ). In particular, satisfaction with and use of virtual visits has been mixed among older adults.…”
Section: Discussionmentioning
confidence: 99%